(3GdJNWjW GdJfajPj s - (3eLjO(B, (3GdcQNjs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2023)
(3jbOe cJGH (B"(3GdJNWjW GdJfajPj(B" (3OdjdkG TGedkG Mhd cjajI JMhjd GdCgOGa GdGSJQGJjLjI Edi NWhGJ YedjI bGHdI ddJfajP(B. (3jHOC GdcJGH HJYQja eaghe GdNWI GdJfajPjI hCSS hVYgG GdUMjMI, Ke jJYeb aj HfGA Gdgjcd GdHQfGeLj hhVY NWI RefjI hehGRfI JaUjdjI ddHQfGeL(B. (3jTQM GdcJGH GdYdGbI GdhKjbI Hjf GdNWI GdJfajPjI hGdNWI GdJTZjdjI, hjbOe feGPL YedjI dHQGeL JfajPjI(B. (3ceG jJWQb Edi JMOjO GdeSJajOjf ef JfajP GdNWI heDTQGJ GdCOGA dbjGS fLGMgG(B. (3hjNJJe GdcJGH HJMdjd GdaLhGJ hYdGbI GdNWI GdJfajPjI HGdCgOGa GdGSJQGJjLjI hGdaQYjI(B. (3HTcd YGe, jgOa GdcJGH Edi JRhjO GdbGQF HCOhGJ hCSGdjH YedjI dUjGZI hJfajP NWW aYGdI JSGge aj JMbjb GdCgOGa GdefThOI(B.s
(3GdeQGLY U(B.52(3, (B63(3,(B81(3, (B98(3,(B110(3,(B129(3,(B139(3,(B152(3,(B163(3,(B177(3,(B200(3,(B211(3,(B231(3,(B253(3,(B273(3,(B297(3,(B316s
Keywords: (3GdEOGQI (B- (3GdJNWjWs; (3GdJNWjW GdGSJQGJjLj (B- (3JfajP GdeTGQjYs; (3GdJNWjW GdJfajPjs